Hegemony Power in George Orwell's Novel Animal Farm - Atmadja, Muhammad David Pamungkas (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2024)
This research explores the theme of power hegemony in George Orwell's novel Animal Farm, focusing on its portrayal of social class. Through a qualitative descriptive research method, the study examines various instances in the novel where power dynamics based on social class are evident. The findings reveal the presence of coercive power and intensive power as forms of hegemony employed by the ruling class. Coercive power is characterized by fear and intimidation, while intensive power involves promising rewards and privileges to maintain control. The research concludes that Animal Farm serves as a vivid depiction of oppression and injustice caused by power imbalances, reflecting the social realities of power dynamics in the real world. The study emphasizes the importance of literature in shedding light on social phenomena and raising awareness about the detrimental effects of hegemonic power structures.